Effect of large constellations on lifetime of satellites in low earth orbits. Issue 3 (September 2017) - Ailor, William; Peterson, Glenn; Womack, James; Youngs, Megan
Abstract: A 2010 study found, assuming business-as-usual satellite operations and replenishment activities, that for large satellites operating in the low Earth orbit (LEO) regime, a mean lifetime reduction over the next 50 years of ∼13% might be expected (i.e., a satellite with a mean lifetime of 10 years in a no-debris environment would see a reduction of 1.3 years in an environment that included space debris), with much of this reduction coming from degradation of solar panels by small, un-trackable debris. Since 2010, proposals have been put forward that would add thousands of new satellites to the LEO environment within the next few years, many more than the number projected in the 2010 study. The current study reexamines the earlier prediction by assuming that over 5000 new small satellites are operating in high LEO orbits, consistent with proposals announced by commercial companies. As with the 2010 study, this projection includes the effects of collisions of both tracked objects, objects greater than 10 cm in LEO, and small debris down to 1 mm—a size that the 2010 study showed could "sandblast" and reduce the power output of solar panels—and adds changes in the debris environment due to the previously un-modeled new satellites colliding in their constellations and with other objects as they undergo constellation replenishment activities. Primary results are that satellites being disposed from or added to the new constellations and debris associated with collisions involving these objects could potentially double the reduction in the mean operational lifetime of satellites operating in LEO. As in the 2010 study, the degradation of solar panels due to small debris impacts is a significant factor in this degradation, with the mean lifetime reduction increasing from the 13% predicted in the earlier study to as much as 60% in some cases (i.e., a large satellite with a mean lifetime of 20 years in a no-debris environment could have its mean lifetime reduced by as much as 12 years). Results suggest that minimizing collisions during replenishment activities and making solar panels and space hardware more resilient to small debris impacts will be increasingly important in the future.